Anjou Vintage Bike (Anjou Vélo Vintage) - Lecomte, Sophie; Metais, Océane (Quality in Sport, 2018)
Abstract Purpose: To show that a local event can have an international reputation. Design / methodology / approach: We will see through the analysis of the routes, the organization of the event and the proposed animations how much Angers velo vintage can have at international and local level Research and practical limitations / implications: We will rely solely on published news articles and researches published. Extrait But: Montrer qu’une manifestion locale peut devenir internationale. Design/methodology/approach: Nous verrons à travers l’analyse des parcours, de l’organisation de la manifestatio et des animations proposés quelle ampleur Angers velo vintage peut avoir au niveau international et local. Research and practical limitations/implications: Nous nous appuierons seulement sur les articles de presse publiés.